2009
DOI: 10.1111/j.1567-1364.2009.00500.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress sensitivity inDebaryomyces hansenii

Abstract: Debaryomyces hansenii is an osmotolerant and halotolerant yeast of increasing interest for fundamental and applied research. In this work, we have performed a first study on the effect of oxidative stress on the performance of this yeast. We have used Saccharomyces cerevisiae as a well-known reference yeast. We show that D. hansenii is much more susceptible than S. cerevisiae to cadmium chloride, hydrogen peroxide or 1,4-dithiothreitol. These substances induced the formation of reactive oxygen species (ROS) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 41 publications
3
27
0
1
Order By: Relevance
“…In this study, we found that the activities of SOD and POD of D. hansenii increased markedly when treated with exogenous calcium (Table 1). Similar results have been reported by Navarrete et al [17], who found that NaCl exerted a protective effect against oxidative stress in D. hansenii. Fig.…”
Section: Discussionsupporting
confidence: 88%
“…In this study, we found that the activities of SOD and POD of D. hansenii increased markedly when treated with exogenous calcium (Table 1). Similar results have been reported by Navarrete et al [17], who found that NaCl exerted a protective effect against oxidative stress in D. hansenii. Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Recent reports have related salt and oxidative stress tolerance in D. hansenii (Navarrete et al ., ; Calderon‐Torres et al ., ). To further investigate the phenotypic differences among the strains in study, tolerance to oxidative stress was checked by exposing the cells to hydrogen peroxide and analyzing their survival along time (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…hansenii is a salt tolerant yeast that somehow uses sodium to protect itself against some abiotic stress factors (Almagro et al, 2000;Papouskova and Sychrova, 2007;Navarrete et al, 2009) and that withstands high levels of intracellular sodium. In fact it has been reported that, for example, in media with low K + , Na + is able to substitute for K + , restoring the specific growth rate (Prista et al, 1997).…”
Section: Discussionmentioning
confidence: 99%